Lyophilization stabilizes clinical‐stage core‐crosslinked polymeric micelles to overcome cold chain supply challenges. Issue 6 (11th February 2021) - Ojha, Tarun; Hu, Qizhi; Colombo, Claudio; Wit, Jan; van Geijn, Michiel; van Steenbergen, Mies J.; Bagheri, Mahsa; Königs‐Werner, Hiltrud; Buhl, Eva Miriam; Bansal, Ruchi; Shi, Yang; Hennink, Wim E.; et al.
Abstract: Background: CriPec technology enables the generation of drug‐entrapped biodegradable core‐crosslinked polymeric micelles (CCPM) with high drug loading capacity, tailorable size, and drug release kinetics. Docetaxel (DTX)‐entrapped CCPM, also referred to as CPC634, have demonstrated favorable pharmacokinetics, tolerability, and enhanced tumor uptake in patients. Clinical efficacy evaluation is ongoing. CPC634 is currently stored (shelf life > 5 years) and shipped as a frozen aqueous dispersion at temperatures below −60°C, in order to prevent premature release of DTX and hydrolysis of the core‐crosslinks. Consequently, like other aqueous nanomedicine formulations, CPC634 relies on cold chain supply, which is unfavorable for commercialization. Lyophilization can help to bypass this issue. Methods and results: Freeze‐drying methodology for CCPM was developed by employing CPC634 as a model formulation, and sucrose and trehalose as cryoprotectants. We studied the residual moisture content and reconstitution behavior of the CPC634 freeze‐dried cake, as well as the size, polydispersity index, morphology, drug retention, and release kinetics of reconstituted CPC634. Subsequently, the freeze‐drying methodology was validated in an industrial setting, yielding a CPC634 freeze‐dried cake with a moisture content of less than 0.1 wt%. It was found that trehalose‐cryoprotected CPC634 could be rapidly reconstituted in less than 5 min at room temperature. Critical quality attributes such as size, morphology, drug retention, and release kinetics of trehalose‐cryoprotected freeze‐dried CPC634 upon reconstitution were identical to those of non‐freeze‐dried CPC634. Conclusion: Our findings provide proof‐of‐concept for the lyophilization of drug‐containing CCPM and our methodology is readily translatable to large‐scale manufacturing for future commercialization. Abstract : We provide a systematically optimized freeze‐drying protocol for clinical‐stage docetaxel‐entrapped core‐crosslinked polymeric micelles (CPC634) identifying trehalose as the most suitable cryoprotectant. Our data, validated in an academic as well as industrial setting, demonstrate the feasibility of lyophilizing core‐crosslinked polymeric micelles which can be readily translatable to large‐scale production for the future commercialization of CriPec technology‐based core‐crosslinked polymeric micelles.